Acute Infusion-Related Side Effects of Amphotericin B Lipid Complex (ABLC) in Oncohematological Patients: Real-World Data from Brazilian Reference Centers - Francelise Bridi Cavassin; Marcello Mihailenko Chaves Magri; Ariela Victoria Borgmann; Isabela Dombeck Floriani; Marina Rachid Barreto; Tania Zaleski; Fabianne Altruda de Moraes Costa Carlesse; Giovanni Luís Breda; Fábio de Araújo Motta; Diego Rodrigues Falci; Ana Verena Almeida Mendes; Hugo Paz Morales; et al. (Infectious Diseases and Therapy)
Abstract Introduction Amphotericin B lipid complex (ABLC) is an effective antifungal agent for treating invasive fungal infections (IFIs) even though its formulation is associated with potential adverse events, including those related to its infusion. This study aimed to analyze the incidence of acute infusion-related side effects (IRSE) associated with ABLC and their relationship with the profile of patients with oncohematological disease admitted in Brazilian reference tertiary hospitals. Methods This is an observational retrospective study that included clinical records of patients hospitalized, in a period of 6 years, diagnosed with probable or proved IFI and treated with at least two doses of ABLC. Results A total of 229 patients were included, with a male prevalence and an average age of 44 years for adults and 10 years for children. Seventy-nine (34.5%) developed some IRSE, 5.1% of which progressed in severe form to discontinuation of treatment. The most prevalent events in adults were fever (66.7%), tremor/chills (53.3%), and tachycardia (24.4%). In children, the most common were fever (64.7%), tremors/chills (50%), and skin rash/itching (17.6%). Statistical significance was found for premedication use from the first dose of ABLC in relation to the onset of infusion reactions (P = 0.006). Multivariate analysis revealed that ABLC, when compared to liposomal AMB (L-AMB), and neutropenia were associated with a higher risk of developing IRSE (odds ratio [OR] 3.04, P = 0.008; and OR 11.02, P = 0.025, respectively). Conclusions The use of premedication was a protective factor against the occurrence of IRSE. Therefore, services providing amphotericin B (AMB) must reinforce protocols or implement new measures that optimize tolerability and safety during the treatment of patients with oncohematological disease, with special attention to patients with neutropenia, prioritizing the liposomal formulation of AMB whenever possible.